Theoretical and experimental study on electron transport in oxygen-plasma-treated monolayer MoS2 - LI, GEN (Trinity College Dublin. School of Physics. Discipline of Physics, 2019)
In recent years, two dimensional (2D) molybdenum disulﬁde (MoS2) has attracted a wide range of interest due to its interesting physics properties, such as valley electronics and quantum spin Hall eﬀect, and its potential applications for the semiconductor industry such as in ﬁeld-eﬀect transistors (FETs) and photodetectors. Chapters 1 to 4 contain background knowledge related to this work, including the crystal structures of MoS2, plasma engineering, density functional theory (DFT) and the transfer matrix method (TMM). In Chapter 5, we introduce the experimental instruments used in this work, including mechanical exfoliation, electron beam lithography (EBL), Atomic Force Microscopy (AFM), Raman and photoluminescene (PL) spectroscopy, and an electric measurement system. In Chapter 6, we utilize radio-frequency oxygen plasma to treat 2D MoS2 FET to enhance the performance of the device. We study the surface morphology of the same device before and after two-second rapid plasma treatment. We ﬁnd that the surface thickness to be doubled after treatment by using AFM. We ﬁnd that both Raman E and A peaks are attenuated. An A exciton peak is quenched and broadened from PL spectroscopy. We further conduct electrical measurements to evaluate the device performance. We ﬁnd that photoresponsivity and mobility are enhanced after 2s of plasma exposure. The threshold voltage of the device shifts to a more negative value, indicating the FET becomes more easily switched on. Moreover, we also utilize polymer encapsulation technique to modify the device. We ﬁnd that polymer protection can improve the device mobility and signiﬁcantly enhance the device stability. The polymer protection technique can further be utilized to realize site-speciﬁc modiﬁcation on MoS2. This Chapter gives insight into surface modiﬁcation and mobility engineering of 2D MoS2 nano devices. In Chapter 7, based on the experimental observations in Chapter 6, we apply DFT to study the electronic and magnetic properties of oxygen-plasma-treated monolayer MoS2. We consider three types of unit cells, which are proposed based on our experimental observation in the Chapter 6. We ﬁrstly optimize the lattice parameters of the studied unit cells. We further combine the three types of unit cell to make various 2 × 2 super cells. By calculating their band structures, we ﬁnd that sulphur vacancies can cause signiﬁcant quenching of band gap and that oxygen adatoms can make the direct band gap of pristine MoS2 to indirect band gap. Moreover, from the spin-dependent DOS, we also ﬁnd that neither sulphur vacancies nor oxygen adatoms can introduce a ferromagnetic phase in to ML MoS2, which is consistent with previous work. Regarding spin-orbit coupling, our calculated SOC strength of pristine MoS2 is consistent with previous work. Oxygen adatoms can cause the location of band splitting to change, which is attributed to the modiﬁcation of band structure by oxygen adatoms. This Chapter gives insight into band-structure engineering and valley electronics of 2D materials. In Chapter 8, we ﬁrstly show how to fabricate MoS2/MoOx heterostructures using a plasma. Then, we study the electron transport in it by TMM. We analyse the tunneling process, in a double-well structure and step-well structure under the condition of electric ﬁeld and no electric ﬁeld. Our work shows that the increasing of transverse momentum will result in the red shift of the resonant peak. We also show that low electric ﬁelds (±0.3 V ) can enhance the magnitude of peaks and intensify the coupling between longitudinal and transverse momentums. However, it can’t optimize the resonant tunnelling condition due to the heavier electron eﬀective mass of MoS2/MoOx heterostructures than that in traditional semiconductor superlattices. Thus, a higher bias is applied and ideal resonant tunnelling peaks are obtained, indicating that negative diﬀerential resistance (NDR) eﬀect can be observed. Moreover, a step-well structure shows a better performance regarding resonant tunnelling than a double-well structure, due to the absence of well separation which can alter the phase of electrons to aﬀect resonant tunnelling condition. This Chapter gives insights into the physics of resonant tunnelling eﬀect and NDR in 2D-materials nano devices, and also sheds light on the design of quantum electronic devices.
APPROVED
Keywords: Monolayer MoS2, plasma treatment, DFT, resonant tunelling effect, electronic band structures